2015
DOI: 10.1136/bmjopen-2014-006510
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco addiction and smoking cessation in Austrian migrants: a cross-sectional study

Abstract: ObjectiveRecent observations revealed substantial differences in smoking behaviour according to individuals’ migration background. However, smoking cessation strategies are rarely tailored on the basis of a migration background. We aimed to determine whether smoking behaviour and preferences for smoking cessation programmes differ between Austrian migrant smokers and Austrian smokers without a migration background.Study designCross-sectional study.SettingRecruitment and interview were performed at public place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Our results draw attention to the lesser binge drinking among migrants compared with the general population in all the three migrant groups in our study, and to more prevalent daily smoking among Russian and Kurdish migrant men compared to the general population. Therefore in the future, the possible treatment gap for harmful substance use among migrants should be evaluated, and the availability of culturally tailored interventions for smoking cessation [ 71 ] and for alcohol use reduction for migrants should be assessed, as proposed in previous literature [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results draw attention to the lesser binge drinking among migrants compared with the general population in all the three migrant groups in our study, and to more prevalent daily smoking among Russian and Kurdish migrant men compared to the general population. Therefore in the future, the possible treatment gap for harmful substance use among migrants should be evaluated, and the availability of culturally tailored interventions for smoking cessation [ 71 ] and for alcohol use reduction for migrants should be assessed, as proposed in previous literature [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, we see that individuals make individual generalizations even in the absence of consistent input in the environment : Categorization and generalization into a symbolic system is simply what humans do when encountering data. (For further discussion, see Archangeli, 2009 ).…”
Section: Categories and Generalizationmentioning
confidence: 99%
“…Due to barriers like insufficient knowledge about healthcare services, language difficulties, and time constraints, migrant populations in Switzerland often fail to access regular smoking cessation treatments, like therapies offered by several providers (e.g., Cancer League, Lung League) [ 11 , 18 , 19 ]. It has also been shown that, in Austria, Turkish-speaking migrants participate less often in counselling programs than Austrian smokers, but are more willing to quit and have more previous cessation trials than Austrian smokers [ 20 ].…”
Section: Introductionmentioning
confidence: 99%